A method for preparing a medical porous titanium alloy implant
The preparation of porous titanium alloy implants through selective laser melting technology solves the problem of excessive elastic modulus of existing titanium alloy implants, achieves matching of mechanical properties with human bones, and improves the stability and service life of the implant.
Patent Information
- Application Number
- CN202310206608.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-03-07
AI Technical Summary
The elastic modulus of existing titanium alloy implants is too high, which leads to mismatch with the mechanical properties of human bones, causing stress shielding, affecting the stability and service life of the implant.
Selected laser melting technology is used to prepare porous titanium alloy implants. By designing a regular hexagonal through-hole structure, the porosity and mechanical properties are regulated and the elastic modulus of the implant is reduced.
The mechanical properties of the implant are matched with the human bones, which reduces the stress shielding phenomenon, improves the stability and service life of the implant, and has a flexible structural design, which can meet different mechanical performance requirements.
Smart Images

Figure HDA0004111133970000011 
Figure HDA0004111133970000012 
Figure HDA0004111133970000021
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a medical porous titanium alloy implant, in particular to a method for preparing a biomaterial by using a selective laser melting technology, and belongs to the technical field of biomedical material preparation. Background Art
[0002] At present, the most widely used metal materials in the medical field such as hard tissue replacement are titanium and titanium alloys; however, the elastic modulus of dense Ti6Al4V (about 105Gp) is significantly higher than that of human bone (1-30GPa), which can easily lead to "stress shielding" phenomenon due to uncoordinated load transfer between the transplant and the host bone. The lack of mechanical stimulation will lead to atrophy of bone tissue and loosening of the implant, and ultimately lead to loosening and fracture of the implant. The pore structure of porous titanium alloy can greatly reduce the elastic modulus of titanium alloy, and its structure is conducive to the growth of bone tissue and cell adhesion. Therefore, people began to focus on the preparation of porous titanium alloy structures.
[0003] There are many methods for preparing porous materials, and the most common ones are powder sintering, slurry foaming, microwave sintering, fiber sintering, etc. The literature (Li Yuxuan, Cui Zhenduo, Yang Xianjin, Zhu Shengli. Porosity characteristics and mechanical properties of porous Ti-Nb-Zr alloy [J]. Functional Materials, 2011, 42 (S1): 92-95.) prepared porous titanium alloy by powder sintering to explore the influence of pore-forming agent on pore characteristics, but it is easy to bring in impurities such as C and O during the sintering process, and the process parameters of the pores need to be determined through more experiments, and the process is complicated; the porous titanium alloy prepared by the slurry foaming method has a high porosity, but it is difficult to control the size of the bubbles in the preparation process, resulting in more internal defects and easy cracks. Although the microwave sintering method has low energy consumption, it cannot prepare precise and complex parts. Similarly, the porous structure prepared by the fiber sintering method also has the disadvantages of more size restrictions and higher cost.
[0004] The invention of patent CN103805797A discloses a method for preparing a medical titanium alloy, which is easy to achieve continuous industrial production through cutting, lamination and vacuum diffusion connection, but it is difficult to accurately control the porosity of the structure, and the sample preparation is single, and the improvement of mechanical properties is not mentioned. The invention of patent CN106756238B uses a medical porous titanium alloy prepared by a vacuum sintering furnace. Although the compressive strength and elastic modulus of the alloy fit human bones, the preparation process is complicated, and the pore size and porosity cannot be accurately controlled. Summary of the invention
[0005] The present invention aims at the stress shielding problem existing in current implants and provides a method for preparing a porous titanium alloy biomaterial; the present invention aims to reduce the elastic modulus of the implant and solve the problem of implant failure caused by mismatch of mechanical properties due to excessively high elastic modulus of the implant.
[0006] The object of the present invention is achieved by the following technical scheme: a method for preparing a medical porous titanium alloy implant, wherein the medical porous titanium alloy has regular hexagonal through holes from top to bottom, which are arranged regularly, and the side length of the unit structure is 0.4-0.7mm, and the wall thickness is 0.2-0.3mm; the pore size can be arbitrarily adjusted;
[0007] The preparation method specifically comprises the following steps:
[0008] (1) Export the model designed by the 3D modeling software as an STL format file, slice the STL 3D model using slicing software, and copy it out.
[0009] (2) The sliced model obtained in step (1) is introduced into the selective laser melting equipment, and Ti6Al4V powder is placed in the powder box of the equipment. The chamber of the equipment is closed and evacuated, and then filled with high-purity argon gas. The electron beam is selectively melted in the high-purity argon atmosphere; after the electron beam finishes scanning one layer, powder is spread; metallurgical forming is performed layer by layer until the structure is formed and printing is completed.
[0010] (3) The porous structure obtained in step (2) is cooled to room temperature in an atmosphere filled with high-purity argon gas and then removed to obtain a porous titanium alloy sample.
[0011] (4) The porous structure obtained in step (3) is placed in a beaker, and alcohol is poured into the beaker to cover the test piece, and then the test piece is placed in an ultrasonic cleaner for cleaning, and then the alcohol is replaced. This is repeated 5-6 times to completely remove excess powder. After cleaning, the test piece is taken out to obtain a medical porous titanium alloy biomaterial.
[0012] The biomaterial of the present invention is prepared from Ti6Al4V powder by selective laser melting, and the density is above 95%. The purity of the Ti6Al4V powder of the present invention is 99.95%.
[0013] The beneficial effects of the present invention are:
[0014] (1) The porous structure of the present invention is a hexagonal honeycomb through-hole structure, the side length of the honeycomb unit structure is 0.4-0.7mm, the wall thickness is 0.2-0.3mm; the porosity is about 50-80%; the mechanical properties are excellent, meeting the pore size and porosity requirements of human implants, and the structure can be designed or customized for specific mechanical or other performance characteristics. Compared with other porous structures, its large surface area, low mass, regular repeating structure and open interconnected pore space have many advantages, which makes the additively manufactured honeycomb structure a highly effective choice for disruptive and improved medical implants.
[0015] (2) The preparation method of the present invention is a selective laser melting technology, which forms a molten pool by applying a high-energy laser beam to the powder, and then rapidly cools and forms the molten pool. Compared with SPS sintering, the smaller laser spot diameter of the selective laser melting technology enables the parts prepared by it to have higher precision, and the parts are not restricted by shape, and can be formed into any complex shape. The pore size, wall thickness, and porosity of the parts can be more accurately controlled, and the preparation process is simple, the formed parts have fine grains, uniform tissue composition, and excellent mechanical properties.
[0016] (3) The large surface area of the structure enhances the ability of the implant to absorb nutrients, and the pores facilitate the transfer of tissue fluid and the ion exchange between the human body and the implant, thereby accelerating the adhesion and growth of bone cells and greatly improving the healing effect of the prosthesis and bone tissue after surgery.
[0017] (4) The molded parts prepared under the process parameters of the present invention have high density (more than 95%), low elastic modulus (12.1-14.4 GPa), and high strength (439.3-591.8 MPa), which perfectly solves the "stress shielding" phenomenon caused by the mismatch between the elastic modulus of artificial implants and human bones (1-30 GPa).
[0018] The porous titanium alloy prepared by the method of the present invention has excellent biocompatibility and mechanical properties, can effectively solve the stress shielding problem, and prolong the service life of the implant, and is an ideal bone repair material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of three-dimensional solid modeling of porous Ti6Al4V biomaterial in Example 1 of the present invention;
[0020] Figure 2 XRD diffraction pattern of the porous Ti6Al4V biomaterial in Example 1 of the present invention;
[0021] Figure 3 Backscattered electron morphology of the porous Ti6Al4V biomaterial in Example 1 of the present invention;
[0022] Figure 4 correspond Figure 2 EDS results; DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the contents described above.
[0024] Example 1
[0025] (1) The model designed by the three-dimensional modeling software is exported as an STL format file, and the STL three-dimensional model is sliced and copied using a slicing software; the pore structure data of the porous titanium alloy are shown in Tables 1 and 2.
[0026] (2) The sliced model obtained in step (1) is introduced into the selective laser melting equipment, and the Ti6Al4V powder is placed in the powder box of the equipment. The chamber of the equipment is closed and evacuated, and then filled with high-purity argon gas. The electron beam is selectively melted in a high-purity argon atmosphere. The laser power parameters are set to 100 W, the scanning speed is 1400 mm / s, the scanning interval is 0.06 mm, and the powder thickness is 0.04 mm. After the electron beam finishes scanning one layer, powder is spread. Metallurgical forming is performed layer by layer until the structure is formed and printing is completed.
[0027] (3) The porous structure obtained in step (2) is cooled to room temperature in an atmosphere filled with high-purity argon gas and then removed to obtain a porous titanium alloy sample.
[0028] (4) The porous structure obtained in step (3) is placed in a beaker, and alcohol is poured into the beaker to cover the test piece, and then the test piece is placed in an ultrasonic cleaner for cleaning, and then the alcohol is replaced, and the process is repeated 5-6 times to completely remove excess powder. After cleaning, a medical porous titanium alloy biomaterial can be obtained.
[0029] The mechanical properties of the porous Ti6Al4V biomaterial prepared in this embodiment were tested to obtain: elastic modulus of 13 GPa, yield strength of 591.8 MPa, compressive strength of 715 MPa, and high material strength, and low elastic modulus, which meets the mechanical compatibility requirements of the implant.
[0030] Example 2
[0031] (1) The model designed by the 3D modeling software is exported as an STL format file, and the STL 3D model is sliced and copied using a slicing software; the pore structure data of the porous titanium alloy are shown in Tables 1 and 2.
[0032] (2) Import the sliced model obtained in step (1) into the selective laser melting equipment, and place the Ti6Al4V powder in the equipment powder box. Close the chamber of the equipment and start to evacuate, then fill it with high-purity argon gas. The electron beam performs selective melting in the high-purity argon atmosphere. Set the laser power parameters to 110W, the scanning speed to 1500mm / s, the scanning interval to 0.05mm, and the powder thickness to 0.04mm. After the electron beam finishes scanning one layer, powder is spread; metallurgical forming is performed layer by layer until the structure is formed and printing is completed.
[0033] (3) The porous structure obtained in step (2) is cooled to room temperature in an atmosphere filled with high-purity argon gas and then removed to obtain a porous titanium alloy sample.
[0034] (4) The porous structure obtained in step (3) is placed in a beaker, and alcohol is poured into the beaker to cover the test piece, and then the test piece is placed in an ultrasonic cleaner for cleaning, and then the alcohol is replaced, and the process is repeated 5-6 times to completely remove excess powder. After cleaning, a medical porous titanium alloy biomaterial can be obtained.
[0035] The mechanical properties of the porous Ti6Al4V biomaterial prepared in this embodiment were tested to obtain: elastic modulus of 12.7 GPa, yield strength of 515 MPa, compressive strength of 642 MPa, and high material strength, and low elastic modulus, which meets the mechanical compatibility requirements of the implant.
[0036] Example 3
[0037] (1) The model designed by the three-dimensional modeling software is exported as an STL format file, and the STL three-dimensional model is sliced and copied using a slicing software; the pore structure data of the porous titanium alloy are shown in Tables 1 and 2.
[0038] (2) Import the sliced model obtained in step (1) into the selective laser melting equipment, and place the Ti6Al4V powder in the equipment powder box, close the chamber of the equipment and start to evacuate, then fill it with high-purity argon gas, and selectively melt the electron beam in the high-purity argon atmosphere. Set the laser power parameters to 120W, the scanning speed to 1700mm / s, the scanning interval to 0.06mm, and the powder thickness to 0.04mm. After the electron beam finishes scanning one layer, spread the powder; metallurgical forming is performed layer by layer until the structure is formed and printing is completed.
[0039] (3) The porous structure obtained in step (2) is cooled to room temperature in an atmosphere filled with high-purity argon gas and then removed to obtain a porous titanium alloy sample.
[0040] (4) The porous structure obtained in step (3) is placed in a beaker, and alcohol is poured into the beaker to cover the test piece, and then the test piece is placed in an ultrasonic cleaner for cleaning, and then the alcohol is replaced, and the process is repeated 5-6 times to completely remove excess powder. After cleaning, a medical porous titanium alloy biomaterial can be obtained.
[0041] The mechanical properties of the porous Ti6Al4V biomaterial prepared in this embodiment were tested to obtain: elastic modulus of 12.1 GPa, yield strength of 439.3 MPa, compressive strength of 538 MPa, and high material strength, and low elastic modulus, which meets the mechanical compatibility requirements of the implant.
[0042] Example 4
[0043] (1) The model designed by the three-dimensional modeling software is exported as an STL format file, and the STL three-dimensional model is sliced and copied using a slicing software; the pore structure data of the porous titanium alloy are shown in Tables 1 and 2.
[0044] (2) The sliced model obtained in step (1) is introduced into the selective laser melting equipment, and Ti6Al4V powder is placed in the powder box of the equipment. The chamber of the equipment is closed and evacuated, and then filled with high-purity argon gas. The electron beam is selectively melted in a high-purity argon atmosphere. The laser power parameters are set to 130 W, the scanning speed is 1800 mm / s, the scanning interval is 0.05 mm, and the powder thickness is 0.04 mm. After the electron beam finishes scanning one layer, powder is spread. Metallurgical forming is performed layer by layer until the structure is formed and printing is completed.
[0045] (3) The porous structure obtained in step (2) is cooled to room temperature in an atmosphere filled with high-purity argon gas and then removed to obtain a porous titanium alloy sample.
[0046] (4) The porous structure obtained in step (3) is placed in a beaker, and alcohol is poured into the beaker to cover the test piece, and then the test piece is placed in an ultrasonic cleaner for cleaning, and then the alcohol is replaced, and the process is repeated 5-6 times to completely remove excess powder. After cleaning, a medical porous titanium alloy biomaterial can be obtained.
[0047] The mechanical properties of the porous Ti6Al4V biomaterial prepared in this embodiment were tested to obtain: elastic modulus of 14.7 GPa, yield strength of 697.5 MPa, compressive strength of 924 MPa, and high material strength, and low elastic modulus, which meets the mechanical compatibility requirements of the implant.
[0048] The three-dimensional solid model of the porous Ti6Al4V biomaterial prepared in Example 1 is as follows Figure 1 As shown, the XRD spectrum is Figure 2 As shown by Figure 2 It can be seen that as the wall thickness of the structure increases, the main phase in the structure is α'.
[0049] The BSEM morphology of the Ti6Al4V biomaterial prepared in Example 1 is as follows Figure 3 As shown in the figure, it can be seen that there are a large number of needle-like phases on the surface of the material, namely α'-Ti; and the structure is uniform and dense, without obvious defects, indicating that this process parameter is better and the molded part is dense; after EDS analysis, such as Figure 4 As shown, the organizational elements are Ti, Al, and V, and the organization is uniform, indicating that this preparation process allows the three elements Ti, Al, and V to diffuse mutually, which is beneficial to the chemical combination between the elements.
[0050] The mechanical properties of the porous Ti6Al4V biomaterial prepared in this embodiment were tested to obtain: elastic modulus of 8.56 GPa, yield strength of 244 MPa, compressive strength of 302 MPa, and high material strength, and low elastic modulus, which meets the mechanical compatibility requirements of the implant.
[0051] According to the method in Examples 1-4, different stent wall thicknesses were used to prepare the mechanical properties of the materials as shown in the following table.
[0052] Table 1
[0053] Honeycomb porous structure design Elastic modulus / GPa Yield strength / MPa Compressive strength / MPa The unit structure has a side length of 0.4mm and a wall thickness of 0.2mm. 13 591.8 715 The unit structure has a side length of 0.5mm and a wall thickness of 0.2mm 12.7 514.9 642 The unit structure has a side length of 0.6mm and a wall thickness of 0.2mm. 12.1 439.3 538 The unit structure has a side length of 0.7mm and a wall thickness of 0.2mm. 14.4 519.9 659
[0054] Table 2
[0055] Honeycomb porous structure design Elastic modulus / GPa Yield strength / MPa Compressive strength / MPa The unit structure has a side length of 0.4mm and a wall thickness of 0.1mm. 13 444.3 611 The unit structure has a side length of 0.4mm and a wall thickness of 0.2mm. 13 591.8 715 The unit structure has a side length of 0.4mm and a wall thickness of 0.3mm 14.7 697.5 924 TC4 solid alloy 105 825 895
[0056] As shown in the table above, when the wall thickness is determined, as the unit side length increases, the elastic modulus and yield strength of the structure show a trend of first decreasing and then increasing. When the unit structure side length is fixed, the elastic modulus and yield strength of the structure increase with the increase of wall thickness. This shows that appropriate design strategies can achieve a balance between porosity and mechanical properties in porous structures. It can not only meet the requirements of implant pore size and porosity, but also make the mechanical properties fit human bones; based on this, the porous material prepared by the above method is a good bone implant material.
Claims
1. A method for preparing a medical porous titanium alloy implant, characterized in that The medical porous titanium alloy has regular hexagonal through holes from top to bottom, which are arranged regularly, and the side length of the unit structure is 0.4-0.7 mm, and the wall thickness is 0.2-0.3 mm; the pore size can be arbitrarily adjusted; The preparation method specifically comprises the following steps: (1) Export the model designed by the 3D modeling software into an STL format file, slice the STL 3D model using slicing software, and copy it out; (2) The sliced model obtained in step (1) is introduced into a selective laser melting device, and Ti6Al4V powder is placed in a powder box of the device. The chamber of the device is closed and evacuated, and then filled with high-purity argon gas. The electron beam selectively melts the sample in a high-purity argon atmosphere. After the electron beam scans one layer, powder is spread. Metallurgical forming is performed layer by layer until the structure is formed and printing is completed. (3) cooling the porous structure obtained in step (2) to room temperature in a high-purity argon atmosphere and then removing it to obtain a porous titanium alloy sample; (4) placing the porous structure obtained in step (3) in a beaker, pouring alcohol into the beaker to cover the test piece, and then placing it in an ultrasonic cleaner for cleaning, and then replacing the alcohol, repeating 5-6 times to completely remove excess powder, and taking it out after cleaning to obtain a medical porous titanium alloy biomaterial; The particle size of titanium alloy powder is between 15 and 53 μm, and the sphericity is good; In step (2), the laser power parameters of the selected area laser melting equipment are 100-130W, the scanning speed is 1400-1800mm / s, the scanning spacing is 0.05-0.06mm, and the powder thickness is 0.04mm; The density of the medical porous titanium alloy biomaterial is above 95%.
2. The method for preparing a medical porous titanium alloy implant according to claim 1, characterized in that: Step (2) The purity of the incoming argon is greater than or equal to 99.999%, and the oxygen concentration is less than 1%.
Citation Information
Patent Citations
Preparation method of medical porous titanium / porous titanium alloy
CN103805797A
A biomedical porous titanium alloy and its preparation method
CN106756238B
Three-dimensional connected honeycomb porous calcium phosphate ceramic artificial bone material and preparation method thereof
CN106518143A
Designing and making method of customized 3D printing porous titanium alloy segmental prosthesis for reconstruction of large segmental bone defect
CN106923936A